THE MAIN PHISIOLOGICAL PROCESSES THAT PARTICIPATE AT THE FORMATION OF THE VEGETAL MASS FOR THE OLT CORN HYBRID - Liviu OLARU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper presents originality by the fact that helps us understand better and special supports the farmers to understand the importance of knowing the main physiological, biochemical and chemical elements which determine the formation of vegetable mass for the corn. In this paper it was studied the Olt corn hybrid which is cultivated on large areas of land especially in the SW area of Oltenia, more precisely on the territory of the Caracal Plain. It is important to remember that on the forming and the welfare of the corn mass depends on the future production. Both the humus reserve in the soil and also the unequal administration of some doses of nitrogen and phosphor determines increased production. It has been watched the vegetation’s state of this hybrid in correlation with the chemical changes of the plants through the use of chemical fertilizers that are correlated also by the cultivation system that had been used so named irrigated and non-irrigated system.